y2-y=6

Move 6 to the left side of the equation by subtracting it from both sides.

y2-y-6=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -6 and whose sum is -1.

-3,2

Write the factored form using these integers.

(y-3)(y+2)=0

(y-3)(y+2)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

y-3=0

y+2=0

Set the first factor equal to 0.

y-3=0

Add 3 to both sides of the equation.

y=3

y=3

Set the next factor equal to 0.

y+2=0

Subtract 2 from both sides of the equation.

y=-2

y=-2

The final solution is all the values that make (y-3)(y+2)=0 true.

y=3,-2

Solve for y y^2-y=6